Analysis of Kirsch’s Problem Using Classical and Micropolar Theory of Elasticity (Proceedings of Faculty of Civil Engineering, 2022)
An analytical analysis of a linear elastic homogeneous and isotropic infinite plate with a circular hole under uniaxial tension (Kirsch’s problem) has been carried out. Experimental results found in available literature have shown that the stress concentration factor at the edge of the hole is always lower than the theoretical prediction based on the classical theory of elasticity. Therefore, the application of the micropolar continuum theory is proposed for a better description of the considered problem. The presented results of the detailed analysis provide a suitable theoretical basis for the further investigation of the micropolar continuum.
Keywords: stress-concentration factor; Kirsch’s problem; micropolar theory; microstructure; material parameters